Prospective test of the developmental propensity model of antisocial behavior: from childhood and adolescence into early adulthood. (2nd December 2017) - Lahey, Benjamin B.; Class, Quetzal A.; Zald, David H.; Rathouz, Paul J.; Applegate, Brooks; Waldman, Irwin D.
Abstract : Background: The developmental propensity model of antisocial behavior posits that several dispositional characteristics of children transact with the environment to influence the likelihood of learning antisocial behavior across development. Specifically, greater dispositional negative emotionality, greater daring, and lower prosociality—operationally, the inverse of callousness— and lower cognitive abilities are each predicted to increase risk for developing antisocial behavior. Methods: Prospective tests of key predictions derived from the model were conducted in a high‐risk sample of 499 twins who were assessed on dispositions at 10–17 years of age and assessed for antisocial personality disorder (APD) symptoms at 22–31 years of age. Predictions were tested separately for parent and youth informants on the dispositions using multiple regressions that adjusted for oversampling, nonresponse, and clustering within twin pairs, controlling demographic factors and time since the first assessment. Results: Consistent with predictions, greater numbers of APD symptoms in adulthood were independently predicted over a 10–15 year span by higher youth ratings on negative emotionality and daring and lower youth ratings on prosociality, and by parent ratings of greater negative emotionality and lower prosociality. A measure of working memory did not predict APD symptoms. Conclusions: These findings support future research on the role of these dispositions in the development of antisocial behavior.